The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/mcp.r113.029744
|View full text |Cite
|
Sign up to set email alerts
|

Using the Ubiquitin-modified Proteome to Monitor Protein Homeostasis Function

Abstract: The ubiquitin system is essential for the maintenance of proper protein homeostasis function across eukaryotic species. Although the general enzymatic architecture for adding and removing ubiquitin from substrates is well defined, methods for the comprehensive investigation of cellular ubiquitylation targets have just started to emerge. Recent advances in ubiquitin-modified peptide enrichment have greatly increased the number of identified endogenous ubiquitylation targets, as well as the number of sites of ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Tryptic digestion efficiency was assessed via SDS-PAGE prior to processing. A mixture of tryptic peptide samples was acidified with trifluoroacetic acid (TFA) to a final concentration of 1% and subsequently desalted using a C 18 Sep-Pak SPE cartridge (Waters, Milford, MA). C 18 cartridges were conditioned with 3 ml of 80% acetonitrile (ACN) followed by 3 ml of 50% ACN (0.1% TFA), and finally 5 ml of 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptic digestion efficiency was assessed via SDS-PAGE prior to processing. A mixture of tryptic peptide samples was acidified with trifluoroacetic acid (TFA) to a final concentration of 1% and subsequently desalted using a C 18 Sep-Pak SPE cartridge (Waters, Milford, MA). C 18 cartridges were conditioned with 3 ml of 80% acetonitrile (ACN) followed by 3 ml of 50% ACN (0.1% TFA), and finally 5 ml of 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
“…In total, we identified 3116 distinct K--GG peptides in 1111 proteins (supplemental Table S2) and obtained a heavy-to-light (H/L) ratio in at least one experiment for 2896 ubiquitin-modified peptides (93% of the total). Multiple studies have identified ubiquitylated peptides in S. cerevisiae, with the recent application of quantitative diGly proteomics yielding thousands of ubiquitylated peptides per study (18,22,23). To evaluate our methodology, we compared our results to a published study that combined ubiquitylated protein enrichment followed by diGly proteomics without SILAC (22).…”
Section: Tul1 E3 Ligase Subunit Genes Show Genetic Interactions With mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic approaches can interrogate the abundance of the endogenous ubiquitin-modified proteome and offer a more unbiased and comprehensive solution to the limitations of using single model substrates to report on UPS activity. Immunoaffinity isolation of the diGlycine (diGLY) ubiquitin remnant remaining after tryptic digestion of ubiquitylated proteins can be utilized to identify and quantify the ub-modified proteome (22,44). Even though this approach does not unambiguously identify ubiquitylated proteins, we will refer to the resulting data as the ub-modified proteome because of the observation that over 94% of all diGLY-modified proteins arise from ubiquitylation events (23).…”
Section: Substantial Proteasome Inhibition Is Required To Block Degramentioning
confidence: 99%
“…The development of quantitative proteomic approaches to interrogate the ubiquitin (ub) 1 -modified proteome provides an opportunity to globally monitor protein homeostasis function without exogenous expression of reporter proteins (22,23). One advantage of the ub-proteomics approach is the ability to interrogate a wide-array of endogenous ubiquitylation events that either target proteins for degradation or regulate protein function without proteasomal targeting.…”
mentioning
confidence: 99%